Meningkatkan Kemampuan Menjelaskan Konsep Listrik Statis Dengan Metode Eksperimen - Msy Fauziah (Universitas Mathla'ul Anwar Banten, 2022)
This study aims to increase interest in learning, learning activities and learning outcomes to explain the concept of static electricity to class IX E SMPN 1 Warunggunung students using experimental methods. The type of research is Classroom Action Research (CAR). This action research was conducted in two cycles in which each cycle contained four components, namely planning, action implementation, observation, and reflection. The results of this study indicate that the application of the experimental method can increase interest in learning, learning activities and learning outcomes to explain the concept of static electricity for class IX E SMPN 1 Warunggunung. This can be seen from the final score of student interest in learning in the first cycle of 3.21, an increase of 0.46 in the second cycle to 3.37, the average percentage of student learning activities in the first cycle of 67.41%, an increase of 9.52 % in the second cycle to 76.66%, student learning outcomes in the first cycle of 78.33, an increase of 9.29 in the second cycle to 87.62. Likewise, the percentage of mastery learning has increased from 59.52%, increased by 33.34% to 92.86%.